The Discourse Structure of Conclusion Section in Indonesian and International Journals - Tiara Azzahra Marpaung; Safnil Arsyad; Azwandi Azwandi (Widya Mandala Surabaya Catholic University, 2022)
In research articles, the conclusion section has an important role because it provides a summary of the overall study and the significance of the findings. However, authors often consider this section less important than other sections in a journal article. The purpose of this study is to investigate the differences and/or the similarities of the rhetorical structure in the conclusions section used in the national journals written by Indonesian authors, non-native speakers, and international journals written by native speakers. This study used a content analysis method using Yang and Allison's model (2003). The data were collected from 60 journal articles from national and international journals articles in Applied Linguistics. The findings show that Move 1 (the summary of the study results) is categorized as obligatory in both national and international journals. Meanwhile, other moves (Move 2 and 3) are classified as conventional and optional because there are significant differences where the frequency is found. This study provides information about rhetorical structure in the conclusions section of research articles to increase the author's awareness of the importance of the three moves in the conclusion section.